Genetic Diversity Analysis of Sweet Potato (Ipomoea Batatas L.) Germplasm from Malaysia and Indonesia Using RAPD Markers - Mohd Shah, Ramisah (2001)
Genetic variation among sweetpotato accession (Ipomoea batatas l.) from Malaysia and Indonesia has not been extensively examined with molecular markers. The objectives of this study are to use random amplified polymorphic DNA (RAPD) marker to determine the degree of polymorphism in the sweetpotato germ plasm and to study the genetiC diversity and relationships among sweetpotato accessions from two different regions, Malaysia and Indonesia. A total of 92 accessions of sweet potato germplasm from the two countries maintained at Universiti Putra Malaysia were characterized using five RAPD· markers. Thirty-nine accessions were collected from seven different states of Malaysia and 53 accessions came from two different sub-regions of Indonesia (Irian Jaya and Java). The results of this study indicated that the levels of polymorphism among all sweetpotato were extremely high. From five random primers used (OPB 07, ope 1 0, OPO 0 1, OPO 06 and OPG 1 4), 1 94 fragments were amplified , of which 1 92 (98. 97%) were polymorphic. Only two fragments were monomorphic. The fragment size ranged from 1 1 7bp - 3 240bp. An NTSYS-pc computer program was further employed for data analysis using Jaccard's coefficient of similarity as a base for dendrogram construction via the U PGMA method. The Jaccard's similarity values ranged from 0.08 to 0.6 9 showing high levels of genetic variability among sweetpotato accessions. The cluster analysis separated Malaysian and Indonesian accessions i nto a d ifferent group with a number of additional clusters. Some of the Malaysian and Indonesian accessions were clustered based on their geographic source. The analysis i ndicates that very large genetic variation exists among sweetpotato accessions used in this study and the sweetpotato collection is a valuable as a genetic resource. This could be done by selecting cultivars from different groups delineated by cluster analysis for hybridization programs. Genetic diversity analysis within the sweetpotato germplasm collection had provided useful i nformation for managing thi s collection. RAPO appears to be useful for discerning variation within crop germplasm and to assess the genetic relationships among sweetpotato germ plasm from Malaysia and Indonesia.